2019
DOI: 10.1039/c9cc04522h
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine cyclic diimides and their polymers

Abstract: We report the formation and degradation of a unique guanidine cyclic diimide (GCDI) structure under mild conditions. Furthermore, the GCDI-based polymers can be readily synthesized from guanidine and dianhydride monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Various pyrimidine analogues 10a-f were synthesized using the method shown in Scheme 2. Initially, benzyl guanidine intermediates 8a-f [66] were obtained by treating 7 [67] with different types of benzyl amines 5a-f bearing -CF3 and -Cl groups. Then, (E)-1-(3,4-dimethoxy phenyl)-3-(dimethylamino) prop-2-en-1-one intermediate 9 was obtained by reacting acetophenone 1 with DMF-DMA under a reflux condition.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Various pyrimidine analogues 10a-f were synthesized using the method shown in Scheme 2. Initially, benzyl guanidine intermediates 8a-f [66] were obtained by treating 7 [67] with different types of benzyl amines 5a-f bearing -CF3 and -Cl groups. Then, (E)-1-(3,4-dimethoxy phenyl)-3-(dimethylamino) prop-2-en-1-one intermediate 9 was obtained by reacting acetophenone 1 with DMF-DMA under a reflux condition.…”
Section: Chemistrymentioning
confidence: 99%
“…Lastly, both the Various pyrimidine analogues 10a-f were synthesized using the method shown in Scheme 2. Initially, benzyl guanidine intermediates 8a-f [66] were obtained by treating 7 [67] with different types of benzyl amines 5a-f bearing -CF Furthermore, we approached the synthesis of substituted diacyl 13a-d and dialkyl CGA cyclohexyl ester analogues 15, 17 as portrayed in Scheme 3. Caffeic acid 11 was Oacylated with acid halide in pyridine in the presence of DMAP catalyst to yield corresponding O-acylated analogues 12a-d.…”
Section: Chemistrymentioning
confidence: 99%
“…The key idea of these strategies is to disrupt the resonance stabilization of the amide group by introducing bulky substituents or electron-withdrawing groups on the amide nitrogen atoms. Recently, our group has reported that guanidine cyclic diimide (GCDI) structures can be readily accessed by reacting guanidines with cyclic anhydrides (Figure b) . Interestingly, the X-ray crystal structure of GCDI revealed that the resonance structure of guanidine is significantly disrupted in the GCDI structure with significantly large Winkler–Dunitz parameters (Figure S1).…”
mentioning
confidence: 99%
“…In the reaction between GCDI 1a and benzyl alcohol in the presence of TFA, we found that N -acylurea 4a was generated as the major product. In contrast, n -butylguanidine was released without the acid as a result of cleavage of the two imide rings . As the neighboring nitrogen in the guanidine structure was substituted with an oxygen atom, we anticipated that the first benzyl alcohol would attack the guanidine carbon center to yield an O -benzyl isourea intermediate and that the second and third alcohols would release dibenzyl ether and open the imide ring, respectively, to form the N -acylurea (Figure S9).…”
mentioning
confidence: 99%
See 1 more Smart Citation